TOWARD INDONESIA’S AGROINDUSTRIES COMPETITIVENESS: THE CASE OF BIOETHANOL DEVELOPMENT FROM SUGARCANE BASED INDUSTRIES - Gita Khaerunisa Indahsari; Rudi Wibowo (UNEJ e-Proceeding, 2012)
World oil price has been fluctuating throughout the years, however the trendcontinue to increase. Due to limited sources of oil production and high demand for worldoil, it is predicted in ten years from 2010, world oil price could even reach as high as tripledigit per barrel. Thus countries around the world have continuously tried to producealternative energy, including Indonesia. The government had been supportive in trying todevelop this industry, including roadmaps and target for alternative energy production, toreduce the dependence on fossil fuel until the next ten years to come. The objective of thispaper is to study the bioethanol industry developed by the PTPN X. The bioethanolindustry is still at its early stage in Indonesia. Problems to develop this industry includesfinding the most potential raw materials used, availability of the industry, stage of 12 and Rudi Wibowocompetition with other uses of the raw materials until end product and marketing. From many potential raw materials, sugarcane is one of the most potential sources of bioethanol.PTPN X case study indicated that bioethanol can be developed along with supportingfactors such resource, technology and company size. The comparative advantage of thePTPN X is the ability to incorporate various problems from upstream to downstream of thesupply chain of bioethanol. Methods such as the EPC, ANP, Diamond Porter Model andcase study of PTPN X are used to demonstrate the potential of sugarcane as an alternativeenergy and the ability of PTPN X to develop this industry.